Locus de control y satisfacción laboral en el personal de Tropa de la Brigada de Infantería N° 7 Loja, periodo 2019 - Martínez Gahona, Dayana Elizabeth (2020)
The present research work has as the objective of determine the relation between Locus of Control and Job Satisfaction in the Squad Troop Staff of the Brigada de Infantería N° 7 of the city of Loja. Locus of Control is considered a variable of personality, that is established as the individual’s behavior and its consequences; while job satisfaction is a combination of psychological, physiological and environmental circumstances that define the behavior that individuals have about their job. This research was developed with a cross-sectional, descriptive-correlational study method, formed by a universe of 120 Troop Staff members of which a sample of 91 participants was selected through the Epi Info 7.1 software. The participants of the study adequately responded to psychological reagents: Rotter Control Locus Scale and Labor Satisfaction Scale. The outcomes revealed a high incidence of Internal Control Locus in the population, as well as a high level of Job Satisfaction; establishing a statistically significant correlation between the variables, that is, having an internal control locus would imply a high level of job satisfaction in Troop Personnel. Bearing in mind that a lower but significant percentage of the inhabitants has low levels of Job Satisfaction, a Psychoeducation Plan was developed with the objective of increasing work motivation and improving the military service that they offer. Keywords: locus of control, personality, job satisfaction, troop personnel, military service.